Research Studies on Pluralism and Multiculturalism - Rosadi, Adi; Aliyah, Adah; Ramayanti, Ani; Ruswandi, Uus (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
The phenomenon observed in the field is the low level of Pluralism and Multiculturalism in schools. The research aims to examine the study of pluralism and multiculturalism. This research adopts a qualitative approach with a descriptive method, specifically a literature review study. The data collection technique used is a literature review. The analysis technique employed is triangulation. The data sources consist of articles related to the study of pluralism and multiculturalism. The research concludes that pluralism and multiculturalism education can be achieved through curriculum development, instructional materials, and social media control, thereby fostering students' awareness and understanding to uphold the values of justice, democracy, humanity, and pluralism in social interactions amidst the diverse national reality